Insights on Fructans and Resistance of Plants to Drought Stress - Benkeblia, Noureddine (Frontiers in Sustainable Food Systems, 2022)
Drought, one of the major abiotic stresses affecting plants, is characterized by a decrease of water availability, resulting in a decrease of the water potential (Ψ) of the cells. One of the strategies of plants in resisting to this low Ψ and related stresses is regulating their water-plant relation and the interplay between Ψsolutes and the turgor pressure (Ψp). This regulation avoids the dehydration induced by low Ψ and is resulting from the accumulation of specific molecules which induce higher tolerance to water deficit and also other mechanisms that prevent or repair cell damages. In plants, fructans, the non-structural carbohydrates (NSC), have other physiological functions than carbon reserve. Among these roles, fructans have been implicated in protecting plants against water deficit caused by drought. As an efficient strategy to survive to this abiotic stress, plants synthesize fructans in response to osmotic pressure in order to osmoregulate the cellular flux, therefore, protecting the membrane damage and maintaining Ψp. Although different studies have been conducted to elucidate the mechanisms behind this strategy, still the concept itself is not well-understood and many points remain unclear and need to be elucidated in order to understand the causal relation between water deficit and fructans accumulation during water scarcity. This understanding will be a key tool in developing strategies to enhance crop tolerance to stressful dry conditions, particularly under the changing climate prediction. This review aims to give new insights on the roles of fructans in the response and resistance of plants to water deficit and their fate under this severe environmental condition.